Anti-Cancer Effects of Synergistic Drug–Bacterium Combinations on Induced Breast Cancer in BALB/c Mice - Subramaniam, Menaga; Arshad, Norhafiza Mohd; Mun, Kein Seong; Malagobadan, Sharan; Awang, Khalijah; Nagoor, Noor Hasima (MDPI, 2019)
Cancer development and progression are extremely complex due to the alteration of various genes and pathways. In most cases, multiple agents are required to control cancer progression. The purpose of this study is to investigate, using a mouse model, the synergistic interactions of anti-cancer agents, 1′-S-1′-acetoxychavicol acetate (ACA), Mycobacterium indicus pranii (MIP), and cisplatin (CDDP) in double and triple combinations to treat chemo-sensitize and immune-sensitize breast cancer. Changes in tumor volume and body weight were monitored. Organs were harvested and stained using hematoxylin-eosin for histopathological assessment. Milliplex enzyme-linked immunosorbent assay (ELISA) was performed to determine cytokine levels, while immunohistochemistry (IHC) was conducted on tumor biopsies to verify systemic drug effects. In vivo mouse models showed tumor regression with maintenance of regular body weight for all the different treatment regimens. IHC results provided conclusive evidence indicating that combination regimens were able to down-regulate nuclear factor kappa-B activation and reduce the expression of its regulated pro-inflammatory proteins. Reduction of pro-inflammatory cytokines (e.g., IL-6, TNF-α, and IFN-γ) levels were observed when using the triple combination, which indicated that the synergistic drug combination was able to significantly control cancer progression. In conclusion, ACA, MIP, and CDDP together serve as promising candidates for further development and for subsequent clinical trials against estrogen-sensitive breast cancer. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.